Pastors and Treasurers: A Case Study of Financial Management in Christian Organization - Dadang Irawan; Anggaripeni Mustikasiwi; Wylen Djap; Oki Hermawati; Erwin Santosa (Sekolah Tinggi Teologi Jaffray Jakarta, 2021)
Prior research has suggested that pastors have difficulty in managing church finances. On the other hand, the involvement of the congregation with knowledge that tends to be pragmatic exposes the pastor to start rubbing against the values ​​contained in this pragmatic understanding, including matters of financial management. In terms of finance, actually the provisions of the Bible are sufficient as guidance, in the form of main values, only requiring an understanding in accordance with the context and the current relevance of the challenges of the church and its congregation. This paper seeks to tell the experience of one of the important actors (informants), a pastor who acts as a ministerial servant of God in pastoral care as well as treasurer in the Indonesian Church Association (PGI). These sources are in the vortex of the tug of interest between idealism as a servant of God and pragmatism, a solution must be sought as soon as possible regarding the sustainability of the church fellowship institution. At the end loyalty, integrity and openness with good intentions to collaborate with various groups (partnering) are the key characters between the roles of pastor and treasurer. This character is preserved in an expression of faith and relying on God. The financial leadership model of a pastor as well as a treasurer with a narrative study approach is described in this article.